ADAT ISTIADAT JAHILIYAH YANG TERLARANG (Analisis Kualitas Hadis tentang Khamar, Judi, dan Aniaya Hewan) - Zulfahmi Zulfahmi (Al-Hikmah Journal for Religious Studies, 2015)
The Hadith of Prophet Muhammad saw, as a source of Islamic teachings, covers almost all aspects of human life. It contains the teachings of a religious ritual as well as the teachings and information related to the daily lifes of human beings. Even the information of some bad behavior happened in the Age of Jahiliyah had become part of the subject that is narrated in the hadith of the Prophet saw. In this paper, the author raise issues about traditions associated with people who lived in the Age of Jahiliyah in hadiths that are prohibited in Islam. Among these traditions was a gambling, harming animals, and drinking the wine, such as the reason for revelation about the prohibition of drinking alcohol, drinking alcohol it self, as well as sanctions for wine drinkers. This study will determine the accuracy all of those hadiths, especially the accuracy in historical perspective. If those hadiths meet the criteria for the validity of the hadith, then they can be used as a source of Islam.